Effect of Luting Materials on the Accuracy of Fit of Zirconia Copings: A Non-Destructive Digital Analysis Method - Berger, Lara; Matta, Ragai; Weiß, Christian; Adler, Werner; Wichmann, Manfred; Zorzin, José Ignacio (Materials, 2024)
The marginal accuracy of fit between prosthetic restorations and abutment teeth represents an essential aspect with regard to long-term clinical success. Since the final gap is also influenced by the luting techniques and materials applied, this study analyzed the accuracy of the fit of single-tooth zirconia copings before and after cementation using different luting materials. Forty plaster dies with a corresponding zirconia coping were manufactured based on a single tooth chamfer preparation. The copings were luted on the plaster dies (n = 10 per luting material) with a zinc phosphate (A), glass–ionomer (B), self-adhesive resin (C), or resin-modified glass–ionomer cement (D). The accuracy of fit for each coping was assessed using a non-destructive digital method. Intragroup statistical analysis was conducted using Wilcoxon signed rank tests and intergroup analysis by Kruskal–Wallis and Mann–Whitney U tests (α = 0.05). Accuracy of fit was significantly different before/after cementation within A (0.033/0.110 µm) and B (0.035/0.118 µm; p = 0.002). A had a significantly increased marginal gap compared to C and D, and B compared to C and D (p ≤ 0.001). Significantly increased vertical discrepancies between A and B versus C and D (p < 0.001) were assessed. Of the materials under investigation, the zinc phosphate cement led to increased vertical marginal discrepancies, whereas the self-adhesive resin cement did not influence the restoration fit.
CRIS-Team Scopus Importer:2024-05-24
Keywords: CAD–CAM technology; ceramics; dental materials; glass–ionomer cement; marginal fit; prosthodontics; resin-modified glass–ionomer cement; self-adhesive resin cement; zinc phosphate cement; zirconia